Lithium iron phosphate material as well as preparation method and application thereof

During the preparation process of lithium iron phosphate material, the reaction of iron powder, reducing agent and iron oxide with phosphoric acid is used to form a lithium iron phosphate precursor and form a tightly packed structure, which solves the problems of low compaction density and degradation of rate performance of lithium iron phosphate materials, and achieves both high compaction density and high rate performance.

CN119735187AActive Publication Date: 2025-04-01TIANJIN RONBAY SKYLAND TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510246287.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-01
Estimated Expiration
2045-03-04

AI Technical Summary

Technical Problem

The low compaction density of existing lithium iron phosphate materials limits its application in the battery field, and increasing the particle size will lead to a decrease in rate performance.

Method used

By adding iron powder and reducing agent to the phosphate to perform the first reaction, a mixed solution is obtained, and then an iron oxide and a lithium source are added for the second reaction to form a lithium iron phosphate precursor, and a lithium iron phosphate material is formed by sintering treatment, so as to achieve mixed blending and tight packing structures of large and small particles.

Benefits of technology

The high compaction density and high rate performance of lithium iron phosphate materials are achieved, and the rate performance and cycle performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735187A_ABST
    Figure CN119735187A_ABST
Patent Text Reader

Abstract

The invention provides a lithium iron phosphate material and a preparation method and application thereof, the preparation method comprises the following steps: adding iron powder and a reducing agent into phosphoric acid, and carrying out first reaction to obtain a mixed solution; adding an iron oxide and a lithium source into the mixed solution, and carrying out a second reaction to obtain a lithium iron phosphate precursor; and sintering the lithium iron phosphate precursor to obtain the lithium iron phosphate material. Wherein the mixed solution comprises iron dihydrogen phosphate and phosphoric acid, and the lithium iron phosphate precursor comprises lithium dihydrogen phosphate, iron hydrogen phosphate and iron oxide. And the iron hydrogen phosphate and the iron oxide have different morphologies, so that the mixing of large and small particles is realized, and a more compact stacking structure is formed, so that the lithium iron phosphate material has high compaction density and high rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a lithium iron phosphate material and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate materials with olivine crystal structure have the advantages of high gram capacity, long cycle life, good safety performance, low price, non-toxic and pollution-free, etc., and are widely used in 3C digital, two-wheeled electric bicycles, electric vehicles, energy storage, batteries and other fields. However, the compaction density of existing lithium iron phosphate materials is low, which limits its application in the battery field.

[0003] At present, the compaction density of lithium iron phosphate materials is mainly improved by increasing the size of the primary particles of lithium iron phosphate or mixing large and small primary particles. However, increasing the size of the primary particles of lithium iron phosphate will lengthen the lithium ion deintercalation path, resulting in a decrease in the rate performance of the lithium iron phosphate material, and thus a decrease in the rate performance of the battery. The mixing of large and small primary particles is generally achieved by mixing particles of different sizes or mixing iron phosphate precursors of different particle sizes through a sand milling process to form a tighter stacking structure and increase the compaction density of the lithium iron phosphate material. However, this method increases the complexity of the production process and the control points of the production process, resulting in large fluctuations between batches and a decrease in the rate performance of the lithium iron phosphate material.

[0004] Therefore, how to provide a preparation method for lithium iron phosphate material having both high compaction density and high rate performance is a technical problem to be solved urgently in this field. Summary of the invention

[0005] The present invention provides a method for preparing a lithium iron phosphate material. The lithium iron phosphate material prepared by the preparation method has both high compaction density and high rate performance. Meanwhile, the preparation method has a simple process and can realize efficient industrial production.

[0006] The present invention also provides a lithium iron phosphate material, which has both high compaction density and high rate performance.

[0007] The present invention also provides a positive electrode sheet, which has both high compaction density and high rate performance.

[0008] The present invention also provides a battery having high rate performance and excellent cycle performance.

[0009] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate material, comprising the following steps:

[0010] (1) adding iron powder and a reducing agent to phosphoric acid to perform a first reaction to obtain a mixed solution;

[0011] (2) adding iron oxide and a lithium source to the mixed solution to carry out a second reaction to obtain a lithium iron phosphate precursor;

[0012] (3) sintering the lithium iron phosphate precursor to obtain the lithium iron phosphate material;

[0013] The mixed solution includes ferric dihydrogen phosphate and phosphoric acid;

[0014] The lithium iron phosphate precursor includes lithium dihydrogen phosphate, iron hydrogen phosphate and iron oxide.

[0015] The preparation method as described above, wherein the molar ratio of the phosphoric acid to the iron powder is z:1, wherein 2<z≤6; and / or,

[0016] The molar ratio of the reducing agent to the iron powder is (0.008-0.013):1.

[0017] The preparation method as described above, wherein the average primary particle size of the iron oxide is 0.05 μm-0.5 μm; and / or,

[0018] The iron oxide includes ferric oxide and / or ferrosinite;

[0019] When the iron oxide comprises ferric oxide, the molar ratio of ferric oxide to iron powder is x1:y1, wherein 0.1≤y1≤0.5, 0.25≤x1≤0.45;

[0020] When the iron oxide includes ferroferric oxide, the molar ratio of ferroferric oxide to iron powder is x2:y2, wherein 0.1≤y2≤0.5, 0.17≤x2≤0.30.

[0021] The preparation method as described above, wherein the process of adding iron powder and a reducing agent to phosphoric acid to carry out a first reaction to obtain a mixed solution comprises: adding iron powder and a reducing agent to a phosphoric acid solution to carry out a first reaction to obtain a mixed solution;

[0022] The mass concentration of the phosphoric acid solution is 30wt%-80wt%; and / or,

[0023] The reducing agent includes one or more of ascorbic acid, citric acid, and glucose; and / or,

[0024] The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium oxalate and lithium acetate.

[0025] The preparation method as described above, wherein the temperature of the first reaction is 70-90° C., and the time of the first reaction is 6-12 h; and / or,

[0026] The temperature of the second reaction is 20-30° C., and the time of the second reaction is 60 min-90 min; and / or,

[0027] The sintering process includes a first sintering process and a second sintering process, and the temperature of the first sintering process is greater than the temperature of the second sintering process;

[0028] In the first sintering treatment, the sintering temperature is 790°C-830°C, and the sintering time is 1-5h;

[0029] In the second sintering treatment, the sintering temperature is 730° C.-790° C., and the sintering time is 8-10 hours.

[0030] The preparation method as described above, wherein the process of adding the iron oxide and the lithium source to the mixed solution and performing a second reaction to obtain the lithium iron phosphate precursor comprises: firstly adding the iron oxide to the mixed solution, stirring to form a suspension, and then adding the lithium source to the suspension, performing a second reaction to obtain the lithium iron phosphate precursor; and / or,

[0031] The process of sintering the lithium iron phosphate precursor to obtain the lithium iron phosphate material also includes: mixing the lithium iron phosphate precursor obtained in step (2) with a carbon source and an additive and grinding them to obtain a grinding slurry, and then sintering the grinding slurry to obtain the lithium iron phosphate material.

[0032] The preparation method as described above, wherein the mass ratio of the carbon source to the lithium iron phosphate precursor is (0.1-0.15): 1; and / or,

[0033] The mass ratio of the additive to the lithium iron phosphate precursor is (0.001-0.008): 1; and / or,

[0034] The carbon source comprises one or more of glucose, sucrose, dextrin, citric acid, fructose, polyethylene glycol, polyvinyl alcohol, and polypropylene glycol; and / or,

[0035] The additive includes a compound containing one or more elements of Al, Mg, Ni, Co, Ti, Cu, Ca, Nb, Cr, Zn, La, Sb, Te, Sr, W, In, and Y; and / or,

[0036] The volume average particle size Dv50 of the grinding slurry is 0.2 μm-0.6 μm.

[0037] In a second aspect, the present invention provides a lithium iron phosphate material obtained by the preparation method described in the first aspect.

[0038] In a third aspect, the present invention provides a positive electrode sheet comprising the lithium iron phosphate material described in the second aspect.

[0039] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet described in the third aspect.

[0040] The lithium iron phosphate material prepared by the above method has high compaction density and high rate performance, thereby improving the rate performance and cycle performance of the battery. The lithium iron phosphate precursor includes lithium dihydrogen phosphate, iron hydrogen phosphate and iron oxide, and the iron hydrogen phosphate and iron oxide have different morphologies, which realizes the mixing of large and small particles and forms a more compact stacking structure, so that the lithium iron phosphate material has both high compaction density and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a SEM image of the lithium iron phosphate precursor of Example 1 of the present invention;

[0042] Figure 2 This is a SEM image of the lithium iron phosphate material of Example 1 of the present invention;

[0043] Figure 3 The button cell assembled with the lithium iron phosphate material of Example 1 of the present invention is subjected to charge and discharge test at rates of 0.5C, 1C and 4C within a voltage range of 2.0V to 3.75V. DETAILED DESCRIPTION

[0044] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0045] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate material, comprising the following steps:

[0046] (1) adding iron powder and a reducing agent to phosphoric acid to perform a first reaction to obtain a mixed solution;

[0047] (2) adding iron oxide and lithium source to the mixed solution to carry out a second reaction to obtain a lithium iron phosphate precursor;

[0048] (3) Sintering the lithium iron phosphate precursor to obtain a lithium iron phosphate material;

[0049] The mixed solution includes ferric dihydrogen phosphate and phosphoric acid;

[0050] The lithium iron phosphate precursor includes lithium dihydrogen phosphate, iron hydrogen phosphate and iron oxide.

[0051] The present invention firstly reacts iron powder, a reducing agent and phosphoric acid to generate a mixed solution (dark green solution) including dihydrogen ferric phosphate and phosphoric acid, wherein the reducing agent can prevent oxidation of iron, improve reaction efficiency and ensure generation of high-purity dihydrogen ferric phosphate; then, iron oxide and a lithium source are added to the mixed solution, and the dihydrogen ferric phosphate and the lithium source undergo a second reaction to obtain a lithium iron phosphate precursor including dihydrogen lithium phosphate, hydrogen ferric phosphate and iron oxide; the hydrogen ferric phosphate and the iron oxide are lithium iron phosphate precursors with different morphologies, and the mixing of large and small particles is achieved to form a more compact stacking structure, thereby improving the compaction density and rate performance of the material; and then, the lithium iron phosphate precursor is sintered to form a lithium iron phosphate material.

[0052] In some embodiments, in step (1), the process of adding iron powder and a reducing agent to phosphoric acid to perform a first reaction to obtain a mixed solution includes: slowly adding iron powder and a reducing agent to phosphoric acid to perform a first reaction to obtain a mixed solution.

[0053] In some embodiments, in step (2), iron oxide and a lithium source are added to the mixed solution, and a second reaction is carried out under stirring to obtain a lithium iron phosphate precursor.

[0054] In some embodiments, in step (3), the process of sintering the lithium iron phosphate precursor further includes: spray drying, sintering and crushing and drying the lithium iron phosphate precursor in sequence to obtain the lithium iron phosphate material. The spray drying can quickly evaporate the liquid in the lithium iron phosphate precursor to obtain lithium iron phosphate precursor particles with uniform particle size distribution, and the crushing and drying can further reduce the particle size of the lithium iron phosphate material.

[0055] The spray drying process and pulverization drying process of the present invention are both conventional processes in the art and are not particularly limited.

[0056] During specific implementation, the sintering process can be carried out in a roller kiln.

[0057] In some embodiments, the molar ratio of phosphoric acid (herein phosphoric acid refers to phosphoric acid solute) to iron powder is z:1, wherein 2<z≤6, so that phosphoric acid can fully react with iron powder to generate dihydrogen phosphate.

[0058] Illustratively, the molar ratio z:1 of phosphoric acid to iron powder may be 2.02:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1, etc.

[0059] In some embodiments, the molar ratio of the reducing agent to the iron powder is (0.008-0.013):1, which can better prevent iron oxidation and promote the reaction of iron powder and phosphoric acid to generate high-purity ferric dihydrogen phosphate.

[0060] Illustratively, the molar ratio of the reducing agent to the iron powder may be 0.008:1, 0.009:1, 0.01:1, 0.011:1, 0.012:1 or 0.013:1, etc.

[0061] According to the technical solution of the present invention, the average primary particle size of the iron oxide is 0.05μm-0.5μm, which helps the iron oxide to be evenly distributed in the mixed solution to form a stable suspension, and has a high specific surface area, which helps to shorten the diffusion path of lithium ions and improve the rate performance of lithium iron phosphate materials.

[0062] Illustratively, the average primary particle size of the iron oxide is 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm or 0.5 μm, which is nano iron oxide.

[0063] In the present invention, the iron oxide includes ferric oxide and / or ferrosinite, that is, the iron oxide may include only ferric oxide, only ferrosinite, or a combination of ferric oxide and ferrosinite.

[0064] In some embodiments, when the iron oxide includes ferric oxide, the molar ratio of ferric oxide to iron powder is x1:y1, wherein 0.1≤y1≤0.5, 0.25≤x1≤0.45.

[0065] Illustratively, the molar ratio of ferric oxide to iron powder is x1:y1, y1 may be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5, etc., and x1 may be 0.25, 0.3, 0.35, 0.4 or 0.45, etc.

[0066] In some embodiments, when the iron oxide includes ferroferric oxide, the molar ratio of ferroferric oxide to iron powder is x2:y2, wherein 0.1≤y2≤0.5, 0.17≤x2≤0.30.

[0067] Illustratively, the molar ratio of ferrosoferric oxide to iron powder is x2:y2, y2 may be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5, etc., and x2 may be 0.17, 0.19, 0.21, 0.23, 0.25, 0.27, 0.29 or 0.3, etc.

[0068] In some embodiments, the process of adding iron powder and a reducing agent to phosphoric acid, performing a first reaction, and obtaining a mixed solution includes: adding iron powder and a reducing agent to a phosphoric acid solution, performing a first reaction, and obtaining a mixed solution.

[0069] In some embodiments, the mass concentration of the phosphoric acid solution is 30 wt %-80 wt %, which helps to ensure the completeness of the first reaction, reduce the generation of by-products, and improve the efficiency of the first reaction.

[0070] Illustratively, the mass concentration of the phosphoric acid solution may be 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt% or 80 wt%, etc.

[0071] In some embodiments, the reducing agent includes one or more of ascorbic acid, citric acid, and glucose, so that the lithium iron phosphate material has better electrochemical properties.

[0072] In some embodiments, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium oxalate, and lithium acetate.

[0073] In the present invention, the temperature of the first reaction is 70-90° C., and the time of the first reaction is 6-12 hours, which can improve the efficiency of the first reaction while saving energy consumption and time cost.

[0074] For example, the temperature of the first reaction may be 70°C, 75°C, 80°C, 85°C, or 90°C, etc.

[0075] For example, the time of the first reaction can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, etc.

[0076] In some embodiments, the temperature of the second reaction is 20-30° C., and the time of the second reaction is 60 min-90 min, which can improve the efficiency of the second reaction and reduce unnecessary side reactions while saving energy consumption and time costs.

[0077] For example, the temperature of the second reaction may be 21° C., 23° C., 25° C., 27° C., or 30° C., etc.

[0078] For example, the second reaction time may be 60 min, 65 min, 70 min, 75 min, 80 min, 85 min or 90 min, etc.

[0079] In some embodiments, the sintering process includes a first sintering treatment and a second sintering treatment. The temperature of the first sintering treatment is greater than the temperature of the second sintering treatment. In the first sintering treatment, the sintering temperature is 790°C-830°C, and the sintering time is 1-5h. In the second sintering treatment, the sintering temperature is 730°C-790°C, and the sintering time is 8-10h. This can improve the crystallinity of the lithium iron phosphate material and promote grain growth and completion of phase change.

[0080] For example, in the first sintering process, the sintering temperature may be 790° C., 800° C., 810° C., 820° C., or 830° C., etc., and the sintering time may be 1 h, 2 h, 3 h, 4 h, or 5 h, etc.

[0081] Illustratively, in the second sintering process, the sintering temperature may be 730° C., 740° C., 750° C., 760° C., 770° C., 780° C. or 790° C., etc., and the sintering time may be 8 h, 9 h or 10 h, etc.

[0082] In some embodiments, sintering is performed under an inert atmosphere to effectively prevent oxidation and maintain the chemical stability of the lithium iron phosphate material. The inert atmosphere includes one of nitrogen, argon, and neon.

[0083] In some embodiments, the process of adding iron oxide and a lithium source to a mixed solution and performing a second reaction to obtain a lithium iron phosphate precursor includes: adding iron oxide to the mixed solution, stirring to form a suspension, and then adding a lithium source to the suspension, performing a second reaction, and obtaining a lithium iron phosphate precursor.

[0084] In some embodiments, the process of sintering the lithium iron phosphate precursor to obtain the lithium iron phosphate material further includes: mixing the lithium iron phosphate precursor obtained in step (2) with a carbon source and an additive and grinding to obtain a grinding slurry, and then drying and sintering the grinding slurry in sequence to obtain the lithium iron phosphate material. The carbon source and the additive can improve the conductivity and electrochemical properties of the lithium iron phosphate material.

[0085] By adjusting the mass ratio of the carbon source to the lithium iron phosphate precursor (referring to the solid component in the lithium iron phosphate precursor), and the mass ratio of the carbon source to the lithium iron phosphate precursor (referring to the solid component in the lithium iron phosphate precursor), the conductivity and electrochemical properties of the lithium iron phosphate material are further improved. In some embodiments, the mass ratio of the carbon source to the lithium iron phosphate precursor is (0.1-0.15):1, and the mass ratio of the additive to the lithium iron phosphate precursor is (0.001-0.008):1.

[0086] Illustratively, the mass ratio of the carbon source to the lithium iron phosphate precursor may be 0.1:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1 or 0.15:1, etc.

[0087] Illustratively, the mass ratio of the additive to the lithium iron phosphate precursor may be 0.001:1, 0.002:1, 0.003:1, 0.004:1, 0.005:1, 0.006:1, 0.007:1 or 0.008:1, etc.

[0088] In some embodiments, the carbon source includes one or more of glucose, sucrose, dextrin, citric acid, fructose, polyethylene glycol, polyvinyl alcohol, and polypropylene glycol, so that the lithium iron phosphate material has better electrochemical properties.

[0089] In some embodiments, the additive includes a compound containing one or more elements of Al, Mg, Ni, Co, Ti, Cu, Ca, Nb, Cr, Zn, La, Sb, Te, Sr, W, In, and Y. The additive includes an oxide containing the above elements. The oxide may include aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, calcium oxide, tungsten oxide, cobalt oxide, etc. The additive can enhance the electronic conductivity of the lithium iron phosphate material and improve the rate performance of the lithium iron phosphate material; at the same time, it can improve the transmission path of lithium ions, reduce ion diffusion resistance, and improve the specific capacity and charge and discharge efficiency of the lithium iron phosphate material.

[0090] In the present invention, the volume average particle size of the grinding slurry (here, the volume average particle size of the solid particles in the grinding slurry) Dv50 is 0.2 μm-0.6 μm, which can further improve the compaction density and rate performance of the lithium iron phosphate material.

[0091] Illustratively, the volume average particle size Dv50 of the polishing slurry may be 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm or 0.6 μm, etc.

[0092] In a second aspect, the present invention provides a lithium iron phosphate material obtained by the preparation method described in the first aspect, wherein the lithium iron phosphate material has both high compaction density and high rate performance.

[0093] In a third aspect, the present invention provides a positive electrode sheet, comprising the lithium iron phosphate material described in the second aspect, and the positive electrode sheet has both high compaction density and high rate performance.

[0094] Specifically, the positive electrode sheet includes a positive electrode collector and a positive electrode active layer located on at least one side surface of the positive electrode collector. Specifically, the positive electrode active layer can be arranged on one side surface of the positive electrode collector in the thickness direction, or the positive electrode active layer can be arranged on the surfaces of the opposite sides in the thickness direction of the positive electrode collector.

[0095] Specifically, the positive electrode active layer includes a lithium iron phosphate material, a conductive agent and a binder. In the positive electrode active layer, the mass percentage of the positive electrode active material can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 93%, 95%, 97%, 99% or a range consisting of any two of them. The mass fraction of the conductive agent can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or a range consisting of any two of them. The mass fraction of the binder can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or a range consisting of any two of them.

[0096] In an embodiment of the present invention, the conductive agent in the positive electrode active layer may be a conventional conductive material in the art. For example, the conductive agent in the positive electrode active layer may include one or more of conductive carbon black, conductive graphite, carbon nanotubes (CNTs), carbon fibers, graphene, acetylene black, and Ketjen black.

[0097] In an embodiment of the present invention, the binder in the positive electrode active layer may be a conventional binding material in the art. For example, the binder in the positive electrode active layer may include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, and the like.

[0098] The embodiment of the present invention may adopt a conventional positive electrode current collector in the art, for example, the positive electrode current collector includes aluminum foil.

[0099] In the embodiment of the present invention, the positive electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the components used to form the positive electrode active layer, such as the positive electrode active material, the conductive agent, and the binder, can be dispersed in a solvent, such as N-methylpyrrolidone (NMP), to prepare a positive electrode slurry, which is then coated on the surface of the positive electrode current collector, and after drying and other processes, the positive electrode sheet is prepared. Among them, the coating, drying and other processes involved are conventional operations for preparing positive electrode sheets by coating, and there is no special limitation on this.

[0100] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet described in the third aspect, and the battery has high rate performance and excellent cycle performance.

[0101] Generally, a battery includes an electrolyte, a battery cell, and a shell that encapsulates the battery cell. The electrolyte is injected into the battery cell in the shell. The battery cell includes a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet. The battery cell can be a laminated battery cell, that is, the battery cell is formed by staggered stacking of positive electrode sheets, separators, and negative electrode sheets; or the battery cell can also be a wound battery cell, that is, the battery cell is formed by stacking positive electrode sheets, separators, and negative electrode sheets and then winding them.

[0102] The electrolyte of the embodiment of the present invention can be a conventional electrolyte in the art. For example, the electrolyte is a non-aqueous electrolyte, which can specifically include an organic solvent and an electrolyte salt. The organic solvent includes, for example, one or more of ethylene carbonate (EC), diethyl carbonate (DEC) and propylene carbonate (PC). The electrolyte salt can include a lithium salt. The lithium salt includes, for example, lithium cobalt oxide, etc., but is not limited thereto.

[0103] In the embodiment of the present invention, the battery cell may be packaged with conventional shell materials in the art, and the shell may include, for example, soft packaging materials such as aluminum-plastic film, but is not limited thereto.

[0104] The embodiments of the present invention can assemble components such as positive electrode sheets, separators and negative electrode sheets into a battery by conventional methods in the art. For example, the positive electrode sheets, separators and negative electrode sheets can be stacked in an alternating manner to produce a stacked battery cell (or wound into a wound battery cell); the battery cell is then placed in a shell (outer packaging), and after conventional processes such as liquid injection (i.e., injecting electrolyte) and packaging, the battery is obtained.

[0105] Hereinafter, the present invention will be further described in detail through specific examples.

[0106] Example 1

[0107] The lithium iron phosphate material of this embodiment is prepared by a method comprising the following steps:

[0108] (1) adding iron powder and ascorbic acid to 50 wt % phosphoric acid, and performing a first reaction at 80° C. for 6 h to obtain a mixed solution of ferric dihydrogen phosphate and phosphoric acid, wherein the molar ratio of phosphoric acid to iron powder is 3:1, and the molar ratio of ascorbic acid to iron powder is 0.01:1;

[0109] (2) adding ferroferric oxide to the mixed solution obtained in step (1), stirring and dispersing the mixture to form a suspension, then slowly adding lithium hydroxide monohydrate to the suspension, and performing a second reaction at 25° C. for 60 minutes to obtain a lithium iron phosphate precursor comprising lithium dihydrogen phosphate, ferric hydrogen phosphate and ferroferric oxide, wherein the molar ratio of ferroferric oxide to iron powder is 0.33:1, and the average primary particle size of the ferroferric oxide is 0.2 μm;

[0110] (3) grinding the lithium iron phosphate precursor, glucose and titanium dioxide obtained in step (2) in a mass ratio of 1:0.13:0.006 to obtain a grinding slurry, wherein the volume average particle size Dv50 of the grinding slurry is 0.35 µm;

[0111] (4) The grinding slurry obtained in step (3) is subjected to spray drying, sintering, and crushing and drying treatment in sequence to obtain a lithium iron phosphate material. The sintering process includes a first sintering treatment and a second sintering treatment under nitrogen protection, the temperature of the first sintering treatment is 810° C., the time of the first sintering treatment is 2 hours, the temperature of the second sintering treatment is 780° C., and the time of the second sintering treatment is 8 hours.

[0112] Example 2

[0113] The preparation method of the lithium iron phosphate material provided in this embodiment is different from that in embodiment 1 in that the average primary particle size of the ferrosoferric oxide in step (2) is 0.3 μm, and the sintering process in step (4) includes a first sintering treatment and a second sintering treatment under nitrogen protection, the temperature of the first sintering treatment is 815° C., the time of the first sintering treatment is 2 h, the temperature of the second sintering treatment is 760° C., and the time of the second sintering treatment is 8 h.

[0114] Example 3

[0115] The method for preparing the lithium iron phosphate material provided in this embodiment is different from that in Embodiment 1 in that the average primary particle size of the ferrosoferric oxide in step (2) is 0.4 μm, and the volume average particle size Dv50 of the grinding slurry in step (3) is 0.30 μm.

[0116] Example 4

[0117] The lithium iron phosphate material of this embodiment is prepared by a method comprising the following steps:

[0118] (1) adding iron powder and ascorbic acid to 60 wt % phosphoric acid, and performing a first reaction at 90° C. for 7 h to obtain a mixed solution of ferric dihydrogen phosphate and phosphoric acid, wherein the molar ratio of phosphoric acid to iron powder is 2.02:1, and the molar ratio of ascorbic acid to iron powder is 0.012:1;

[0119] (2) adding ferric oxide to the mixed solution obtained in step (1), stirring and dispersing the mixture to form a suspension, then slowly adding lithium hydroxide monohydrate to the suspension, and performing a second reaction at 25° C. for 80 min to obtain a lithium iron phosphate precursor comprising lithium dihydrogen phosphate, ferric hydrogen phosphate and ferric oxide, wherein the molar ratio of ferric oxide to iron powder is 0.5:1, and the average primary particle size of the ferric oxide is 0.35 μm;

[0120] (3) grinding the lithium iron phosphate precursor, carbon source and vanadium pentoxide obtained in step (2) in a mass ratio of 1:0.12:0.003 to obtain a grinding slurry; wherein the carbon source includes glucose and polyethylene glycol (the weight average molecular weight of polyethylene glycol is 6000-8000), the mass ratio of glucose to polyethylene glycol is 2:1, and the volume average particle size Dv50 of the grinding slurry is 0.4 µm;

[0121] (4) The grinding slurry obtained in step (3) is subjected to spray drying, sintering, and crushing and drying treatment in sequence to obtain a lithium iron phosphate material. The sintering process includes a first sintering treatment and a second sintering treatment under nitrogen protection, the temperature of the first sintering treatment is 815° C., the time of the first sintering treatment is 1 hour, the temperature of the second sintering treatment is 770° C., and the time of the second sintering treatment is 9 hours.

[0122] Example 5

[0123] The preparation method of the lithium iron phosphate material provided in this embodiment is different from that in Example 4 in that the temperature of the first reaction in step (1) is 80°C, the average primary particle size of ferric oxide in step (2) is 0.6 μm, and in step (3), the volume average particle size Dv50 of the grinding slurry is 0.7 μm.

[0124] Example 6

[0125] The preparation method of the lithium iron phosphate material provided in this embodiment is different from that in Example 1 in that in step (2), lithium hydroxide monohydrate is replaced by lithium carbonate, and in step (4), titanium dioxide is replaced by magnesium oxide, and the mass ratio of the lithium iron phosphate precursor, glucose and magnesium oxide is 1:0.15:0.001.

[0126] Example 7

[0127] The preparation method of the lithium iron phosphate material provided in this embodiment is different from that in Example 1 in that, in step (2), the average primary particle size of ferrosoferric oxide is 0.05 μm, and lithium hydroxide monohydrate is replaced by lithium acetate. In step (3), the volume average particle size Dv50 of the grinding slurry is 0.2 μm. In step (4), glucose is replaced by citric acid, and titanium dioxide is replaced by aluminum oxide.

[0128] Example 8

[0129] The method for preparing the lithium iron phosphate material provided in this embodiment is different from that in Embodiment 1 in that, in step (2), the average primary particle size of ferrosoferric oxide is 0.6 μm, and in step (3), the volume average particle size Dv50 of the grinding slurry is 0.7 μm.

[0130] Example 9

[0131] The preparation method of the lithium iron phosphate material provided in this embodiment is basically the same as that in Embodiment 1, except that the first reaction in step (1) is carried out at 60°C.

[0132] Example 10

[0133] The preparation method of the lithium iron phosphate material provided in this embodiment is basically the same as that in embodiment 1, except that the sintering conditions in step (4) are: keeping the temperature at 780° C. for 8 h under nitrogen protection.

[0134] Embodiment 11

[0135] The preparation method of the lithium iron phosphate material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the molar ratio of the reducing agent to the iron powder is 0.016:1.

[0136] Comparative Example 1

[0137] The preparation method of the lithium iron phosphate material provided in this comparative example is basically the same as that of Example 1, except that the molar ratio of iron powder to phosphoric acid is 1:1, and ferrosoferric oxide is not used.

[0138] Comparative Example 2

[0139] The preparation method of the lithium iron phosphate material provided in this comparative example is basically the same as that of Example 1, except that no iron powder is used and the molar ratio of ferrosoferric oxide to phosphoric acid is 1:3.

[0140] Comparative Example 3

[0141] The preparation method of the lithium iron phosphate material in this comparative example is different from that in Example 1 in that the order of adding ferroferric oxide is changed, and the specific steps are as follows:

[0142] (1) adding iron powder, ferroferric oxide and ascorbic acid to 50 wt % phosphoric acid, and performing a first reaction at 80° C. for 6 h to obtain a mixed solution of ferric dihydrogen phosphate, iron oxide and phosphoric acid, wherein the molar ratio of phosphoric acid to iron powder is 3:1, the molar ratio of ascorbic acid to iron powder is 0.01:1, the molar ratio of ferroferric oxide to iron powder is 0.33:1, and the average primary particle size of ferroferric oxide is 0.2 μm;

[0143] (2) slowly adding lithium hydroxide monohydrate to the mixed solution, and performing a second reaction at 25° C. for 60 minutes to obtain a lithium iron phosphate precursor including lithium dihydrogen phosphate, ferric hydrogen phosphate and ferrosoferric oxide;

[0144] (3) grinding the lithium iron phosphate precursor, glucose and titanium dioxide obtained in step (2) in a mass ratio of 1:0.13:0.006 to obtain a grinding slurry, wherein the volume average particle size Dv50 of the grinding slurry is 0.35 µm;

[0145] (4) The grinding slurry obtained in step (3) is subjected to spray drying, sintering, and crushing and drying in sequence to obtain a lithium iron phosphate material. The sintering process includes a first sintering process and a second sintering process under nitrogen protection, the temperature of the first sintering process is 810° C., the time of the first sintering process is 2 hours, the temperature of the second sintering process is 780° C., and the time of the second sintering process is 8 hours.

[0146] Application Examples and Comparative Examples

[0147] Dissolve polyvinylidene fluoride (PVDF) in N-methyl-pyrrolidone to prepare a PVDF solution with a concentration of 0.2 g / L. According to the mass ratio of lithium iron phosphate material, conductive carbon black and PVDF of 92:5:3, weigh the lithium iron phosphate material, conductive carbon black and PVDF solution prepared in the above embodiment and comparative example, mix and stir to form a slurry mixture, evenly coat the slurry mixture on aluminum foil, dry at 80°C for 30 minutes, cut into circular positive electrode sheets, and dry at 120°C in a vacuum oven for 8 hours. In an argon atmosphere glove box with a water content of <1ppm and an oxygen content of <1ppm, place the above positive electrode sheet (surface density of 70g / m 2 ), negative electrode Li metal disc, 1 mol / L lithium cobalt oxide electrolyte (solvent is ethylene carbonate), and a 2025 type button battery shell are used to assemble a button battery.

[0148] Performance Test:

[0149] (1) Compacted density: Take a positive electrode sample (specifically, the positive electrode sample can be cut by a cutter to obtain a positive electrode sample of suitable size), test the total mass m1 of the positive electrode sample, the total thickness T1 of the positive electrode sample (T1 = the total thickness of the positive electrode active layer + the thickness of the positive electrode current collector. When the positive electrode active layer is provided on both the front and back surfaces of the positive electrode current collector, the total thickness of the positive electrode active layer = the thickness of the positive electrode active layer on one surface of the positive electrode current collector + the thickness of the positive electrode active layer on the other surface of the positive electrode current collector), and the surface area S of the single side of the positive electrode sample in the thickness direction; then scrape off the positive electrode active layer on the positive electrode sample, test the mass m2 of the positive electrode current collector, and the thickness T2 of the positive electrode current collector, then the total thickness of the positive electrode active layer = T1-T2, the surface density of the positive electrode active layer = (m1- m2) / S, the compaction density of the positive electrode active layer = the surface density of the positive electrode active layer / the total thickness of the positive electrode active layer = (m1-m2) / (S×(T1-T2)).

[0150] (2) 0.5C (1C = 170mAh / g) rate performance test: At room temperature (25°C), the button cells of the application example and the comparative example were charged to 3.75V at a constant current of 0.5C, and then charged to a current of 0.02C at a constant voltage of 3.75V. The button cells were left for 5 min to stabilize the chemical state; then they were discharged to 2.0V at a constant current of 0.5C. The above charge and discharge process was repeated twice, and the average value of the discharge capacity obtained twice was recorded. The test results are shown in Table 1.

[0151] (3) 1C rate performance test: At room temperature (25°C), the battery was charged to 3.75V at a constant current of 0.5C, then charged to a current of 0.02C at a constant voltage of 3.75V, and left for 5 min; then discharged to 2.0V at 0.5C, and cycled twice; then the battery was charged to 3.75V at a constant current of 1C, then charged to a current of 0.02C at a constant voltage of 3.75V, and left for 5 min; then discharged to 2.0V at 1C, and cycled twice. The average 1C capacity obtained after two cycles was recorded. The test results are shown in Table 1.

[0152] (4) 4C rate performance test: At room temperature (25°C), the battery was charged to 3.75V at a constant current of 0.5C, then charged to a current of 0.02C at a constant voltage of 3.75V, and left for 5 min; then discharged to 2.0V at 0.5C, and cycled twice; then the battery was charged to 3.75V at a constant current of 4C, then charged to a current of 0.02C at a constant voltage of 3.75V, and left for 5 min; then discharged to 2.0V at 4C, and cycled twice. The average 4C capacity obtained after two cycles was recorded. The test results are shown in Table 1.

[0153] Table 1

[0154]

[0155] like Figure 1 As shown, the lithium iron phosphate precursor in Example 1 achieves mixing of large and small particles, forming a dense stacking structure. Figure 2 As shown, the lithium iron phosphate material obtained by sintering the lithium iron phosphate precursor in Example 1 also achieves mixing of large and small particles and has a more compact stacking structure.

[0156] like Figure 3 As shown, the button cell assembled with lithium iron phosphate material in Example 1 has a higher specific capacity in the voltage range of 2.0V to 3.75V and a smaller attenuation, indicating that the lithium iron phosphate material has excellent rate performance.

[0157] From the analysis of Table 1, it can be seen that by comparing Examples 1-11 with Comparative Examples 1-3, the lithium iron phosphate material in Examples 1-11 has a higher compaction density, and the button-type battery containing the lithium iron phosphate material in Examples 1-11 has a higher specific discharge capacity. This shows that the hydrogen iron phosphate and the iron oxide in the lithium iron phosphate precursor prepared by the preparation method of the present invention have different morphologies, and the mixing of large and small particles is achieved to form a more compacted structure, so that the lithium iron phosphate material has both high compaction density and high rate performance.

[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a lithium iron phosphate material, characterized in that: The following steps are involved: (1) adding iron powder and a reducing agent to phosphoric acid to perform a first reaction to obtain a mixed solution; (2) adding iron oxide and a lithium source to the mixed solution to carry out a second reaction to obtain a lithium iron phosphate precursor; (3) sintering the lithium iron phosphate precursor to obtain the lithium iron phosphate material; The mixed solution includes ferrous dihydrogen phosphate and phosphoric acid; The lithium iron phosphate precursor includes lithium dihydrogen phosphate, iron hydrogen phosphate and iron oxide.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the phosphoric acid to the iron powder is z:1, wherein 2<z≤6; and / or, The molar ratio of the reducing agent to the iron powder is (0.008-0.013):

1.

3. The preparation method according to claim 1, characterized in that: The average primary particle size of the iron oxide is 0.05 μm-0.5 μm; and / or, The iron oxide includes ferric oxide and / or ferrosinite; When the iron oxide comprises ferric oxide, the molar ratio of ferric oxide to iron powder is x1:y1, wherein 0.1≤y1≤0.5, 0.25≤x1≤0.45; When the iron oxide includes ferroferric oxide, the molar ratio of ferroferric oxide to iron powder is x2:y2, wherein 0.1≤y2≤0.5, 0.17≤x2≤0.

30.

4. The preparation method according to claim 1, characterized in that: The process of adding iron powder and a reducing agent to phosphoric acid to perform a first reaction to obtain a mixed solution comprises: adding iron powder and a reducing agent to a phosphoric acid solution to perform a first reaction to obtain a mixed solution; The mass concentration of the phosphoric acid solution is 30wt%-80wt%; and / or, The reducing agent includes one or more of ascorbic acid, citric acid, and glucose; and / or, The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium oxalate and lithium acetate.

5. The preparation method according to claim 1, characterized in that: The temperature of the first reaction is 70-90° C., and the time of the first reaction is 6-12 hours; and / or, The temperature of the second reaction is 20-30° C., and the time of the second reaction is 60 min-90 min; and / or, The sintering process includes a first sintering process and a second sintering process, and the temperature of the first sintering process is greater than the temperature of the second sintering process; In the first sintering process, the sintering temperature is 790°C-830°C, and the sintering time is 1-5h; In the second sintering treatment, the sintering temperature is 730° C.-790° C., and the sintering time is 8-10 hours.

6. The preparation method according to claim 1, characterized in that: The process of adding iron oxide and lithium source to the mixed solution and performing a second reaction to obtain a lithium iron phosphate precursor comprises: firstly adding iron oxide to the mixed solution, stirring to form a suspension, then adding a lithium source to the suspension, performing a second reaction, and obtaining the lithium iron phosphate precursor; and / or, The process of sintering the lithium iron phosphate precursor to obtain the lithium iron phosphate material also includes: mixing the lithium iron phosphate precursor obtained in step (2) with a carbon source and an additive and grinding them to obtain a grinding slurry, and then drying and sintering the grinding slurry in sequence to obtain the lithium iron phosphate material.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the carbon source to the lithium iron phosphate precursor is (0.1-0.15): 1; and / or, The mass ratio of the additive to the lithium iron phosphate precursor is (0.001-0.008): 1; and / or, The carbon source comprises one or more of glucose, sucrose, dextrin, citric acid, fructose, polyethylene glycol, polyvinyl alcohol, and polypropylene glycol; and / or, The additive includes a compound containing one or more elements of Al, Mg, Ni, Co, Ti, Cu, Ca, Nb, Cr, Zn, La, Sb, Te, Sr, W, In, and Y; and / or, The volume average particle size Dv50 of the grinding slurry is 0.2 μm-0.6 μm.

8. A lithium iron phosphate material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: The invention comprises the lithium iron phosphate material obtained by the preparation method according to any one of claims 1 to 7 or the lithium iron phosphate material according to claim 8.

10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of low-cost lithium iron phosphate

    CN110482515A

  • Preparation method of lithium iron phosphate positive electrode material and lithium ion battery

    CN115557482A

  • Preparation method of lithium iron phosphate, positive active material, positive pole piece, battery and electric device

    CN117088352A

  • Lithium manganese iron phosphate composite material as well as preparation method and application thereof

    CN117790731A

  • Method for preparing high performance lithium iron phosphate nanopowder

    US20240034626A1

Cited By

  • Lithium iron phosphate material and preparation method therefor and use thereof

    WO2026184043A1